PWE-153 Prognostic significance of gastrointestinal stromal tumour (gist) associated alarm symptoms at presentation. (22nd June 2015) - Garrod, H; Wheat, J; Davies, L; Lewis, W
Abstract : Introduction: NICE referral guidelines for suspected upper gastrointestinal (UGI) cancer have recommended the use of alarm symptoms (AS) to direct patient referral, but their value with regard to the rarer UGI GISTs are unknown. The aim of this study was to establish whether the number and nature of patients' symptoms at presentation was related to prognosis. Method: Consecutive 161 GIST patients [86 male, median age 66 (20–91) yr, 74% gastric, 15% small bowel, 3.8% colorectal, 2.5% oesophagus, 4.7% other] were studied prospectively and the presence of AS at diagnosis was recorded. The primary outcome measure was survival. Results: One hundred and twenty patients (74.5%) were symptomatic at presentation but 41 patients (25.5%) had GISTs diagnosed that were incidental findings. Of the symptomatic patients 83 (51.6%) had AS, the commonest of which was GI bleeding, 45 patients (28%). Overall 5 and 10 year survival was 79% and 53%, but was significantly poorer for patients presenting with AS; 5 and 10 yr survival for those with AS was 75% and 44%, compared with 85% and 72% without AS (Chi 2 17.465, p < 0.0001). On multivariable analysis, the only independent symptomatic factor associated with survival was the AS of weight loss at presentation (HR 4.214, 95% CI 3.130 to 5.298, p = 0.008). Conclusion: The presence and nature of GIST presenting symptoms and alarm symptoms in particular is an important prognostic indicator. Disclosure of interest: None Declared.